Company’s financial performance before and after registering on Indonesia Sharia Stock Index - Ari Prasetyo, Ventira Dwi Insani, (Opción, 2020)
This study aims to analyze the company’s financial performance before and after being listed on the Indonesian Sharia Stock Index (ISSI). This research applied a quantitative method. The data in this study are 10 companies from all companies that are registered on the ISSI. Purposive sampling technique was applied to obtain the target sample. The results showed there were differences in financial performance in terms of solvency ratios before and after the company was registered at ISSI. In conclusion, there was a change in the company’s solvency ratio before and after being registered on ISSI.